Circular RNAs: New players involved in the regulation of cognition and cognitive diseases - Yu, Xiaohan; Liu, Haoyu; Chang, Ning; Fu, Weijia; Guo, Zhiwen; Wang, Yue (Frontiers in Neuroscience, 2023)
Circular RNAs (circRNAs), a type of covalently closed endogenous single-stranded RNA, have been regarded as the byproducts of the aberrant splicing of genes without any biological functions. Recently, with the development of high-throughput sequencing and bioinformatics, thousands of circRNAs and their differential biological functions have been identified. Except for the great advances in identifying circRNA roles in tumor progression, diagnosis, and treatment, accumulated evidence shows that circRNAs are enriched in the brain, especially in the synapse, and dynamically change with the development or aging of organisms. Because of the specific roles of synapses in higher-order cognitive functions, circRNAs may not only participate in cognitive functions in normal physiological conditions but also lead to cognition-related diseases after abnormal regulation of their expression or location. Thus, in this review, we summarized the progress of studies looking at the role of circRNA in cognitive function, as well as their involvement in the occurrence, development, prognosis, and treatment of cognitive-related diseases, including autism, depression, and Alzheimer’s diseases.